2015
DOI: 10.1021/tx5003518
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Atheroprotective Effects of Gossypetin against Endothelial Cell Injury by Induction of Autophagy

Abstract: Oxidized low-density lipoprotein (ox-LDL) contributes to the pathogenesis of atherosclerosis by promoting vascular endothelial cell injury.Gossypetin, a naturally occurring hexahydroxyflavone, has been shown to possess antimutagenic, antioxidant, antimicrobial, and antiatherosclerotic effects. In this study, the atheroprotective role of gossypetin was examined in endothelial cells. The protective effect of gossypetin against ox-LDL-induced injury in human umbilicalvein endothelial cells (HUVECs) was first note… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 52 publications
4
32
0
Order By: Relevance
“…Our results demonstrated that GTIN treatments induced a significant cell cycle arrest at G0/G1 phase in LNCaP cell, but its apoptosis‐inducing effect was lower than DU145 cells (Figure C and Figure ). This is consistent with previous observation that GTIN possesses only weak cytotoxicity and inhibited the proliferation of human pulmonary epithelial cells, murine macrophage cells, and human umbilical vein endothelial cells (HUVECs) without causing cell death . Collectively, these findings indicate that the inhibitory effect of GTIN on the growth of LNCaP cells may be contributed by the induction of cell cycle arrest, apoptosis or others.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results demonstrated that GTIN treatments induced a significant cell cycle arrest at G0/G1 phase in LNCaP cell, but its apoptosis‐inducing effect was lower than DU145 cells (Figure C and Figure ). This is consistent with previous observation that GTIN possesses only weak cytotoxicity and inhibited the proliferation of human pulmonary epithelial cells, murine macrophage cells, and human umbilical vein endothelial cells (HUVECs) without causing cell death . Collectively, these findings indicate that the inhibitory effect of GTIN on the growth of LNCaP cells may be contributed by the induction of cell cycle arrest, apoptosis or others.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, it is still a matter of debate as to whether natural products, such as resveratrol, not only suppress cancer cells by activating apoptosis but also protect normal cells from oxidative injury via autophagy induction . In agreement with these previous studies, the findings from our study reveal that GTIN at higher dosage range induced not only apoptosis (≥50 μM) but also autphagic cell death (25 μM) in LNCaP cells (Figures ‐), and, on the other hand, lower concentrations (0.1‐0.5 μM) had a protective effect via autophagy induction in HUVECs . The findings, hence, provided evidences supporting a multifunction of GTIN on LNCaP cells and HUVECs between high and low concentrations.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In advanced AS, plaque rupture or erosion may cause acute clinical events. However, in early AS with endothelial dysfunction (33), the repair of VEC injuries may prevent the subsequent development of AS. Furthermore, in advanced AS, apoptotic macrophages may be quickly cleaned-up by macrophages, to prevent the progression of inflammation and plaque necrosis, thereby delaying plaque development (29).…”
Section: Autophagy In Asmentioning
confidence: 99%